Pengaruh Mc Kenzie Exercise terhadap Tingkat Nyeri Punggung Bawah pada Pengrajin Batik di Kecamatan Laweyan - Amelia Ayu Kusuma Wardhani; Riyani Wulandari (Jurnal Rumpun Ilmu Kesehatan, 2024)
Low back pain is one of the diseases that contributes greatly to disability. The World Health Organization (WHO) states that the incidence of low back pain is 619 million people throughout the world and is expected to increase to 843 million cases in 2050. One of the interventions that supports this is Mc Kenzie Exercise therapy to treat lower back pain. The aim of this research was to determine the effect of the Mc Kenzie Exercise on the level of lower back pain in batik craftsmen. This research method is a type of Pre-Experimental research with a One-Group Pre Test-Post Test Design. Using a sampling technique in the form of non-probability sampling, namely the purposive sampling method. Sample of 15 batik craftsmen. Mc Kenzie Exercise is done 8x for 4 weeks. Data analysis used was the Wilcoxon sign rank test. The results of this research, before the intervention was carried out, most batik craftsmen experienced moderate pain with a percentage of 46.7%, after the intervention it decreased to mild pain with a percentage of 53.3%, and the Wilcoxon test results showed a p-value of 0.005 < 0.05, which means There is an effect of Mc Kenzie Exercise on reducing lower back pain. The conclusion of this research is that the Mc Kenzie Exercise has the effect of reducing lower back pain in batik craftsmen.